Validation of Pesticides Multi-Residual Testing Method on Nutmeg by Using UPLC-MS/MS - Bayu Refindra Fitriadi (Walisongo Journal of Chemistry, 2021)
The use of pesticides in nutmeg still leaves an accumulation of pesticide residues that can endanger human health and damage the ecological balance. In addition, nutmeg with high pesticide residue content will be rejected by nutmeg export destination countries. This research was conducted to validate the method of testing pesticide residues of carbaryl, carbofuran, acetate, and dimethoate on nutmeg. This pesticide residue test uses the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) optimization method and is analyzed using UPLC-MS/MS (Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry). This method meets the validation requirements according to SANTE/12682/2019. The limit of quantification (LOQ) of the analyte is below the Maximum Residue Limit (MRL) set by the European Union through Regulation (EC) No. 396/2005.